Cytotoxic effect of indigenously fabricated dental magnets for application in prosthodontics - Satyabodh Shesharaj Guttal; Ramesh K Nadiger; Pravinkumar Shetty (Wolters Kluwer Medknow Publications, 2018)
Context: Dental magnets are used for retaining removable prostheses such as a removable partial denture, complete denture, and maxillofacial prosthesis. They provide good retention for the prostheses. However, the elements released from the magnets may be cytotoxic for the tissues. Therefore, it is necessary to evaluate their cytotoxic effect on cell lines. Aim: The aim of the study is to check the cytotoxic effect of indigenously fabricated dental magnets on animal cell lines. Materials and Methods: Neodymium-iron-boron (Nd-Fe-B) magnet was tested for cytotoxicity. The magnet was encased in a teflon cylinder. Magnets were placed in the well tissue-cultured plates together with a suspension containing NIH 3T3 mouse fibroblasts (5 × 105 cells/ml). After 3 days of incubation at 37°C, cell viability was determined by mean transit time (MTT) assay. Cells were subsequently dissolved in 100 μl dimethyl sulfoxide with gentle shaking for 2 h at room temperature followed by measurement of absorbance at 570 nm. Eight replicate wells were used at each point in each of four separate measurements. Measured absorbance values were directly used for calculating percent of viable cells remaining after the respective treatment. Data were analyzed statistically with significance level set at P < 0.05. Results: The control group had highest absorbance reading for the MTT assay followed by test group. The lowest values were found with bare Nd-Fe-B magnets. One-way ANOVA test was performed for the data obtained. There was a statistical significant difference seen in the positive control (bare magnets, 44.96) and the test (teflon cased magnets, 96.90) group. Conclusion: More number of viable cells was visible in test group cells indicating that the indigenously fabricated dental magnet did not show any cytotoxicity.